The perspectives of women on sustainable fashion consumption: Comparative study of university teachers and students - Živilė Stankevičiūtė; Ieva Jarmalavičiūtė (PLoS ONE, 2025)
In the recent decade, fashion industry has been receiving extensive criticisms for having a significant negative impact on the environment and people. As the counterpoint of rapid pace and cheap prices which trigger overconsumption, sustainable fashion started turning into a new trend and demand for business. As the interest of consumers in sustainability continues to grow, the literature started analysing what drives or hinders them from sustainable consumption. However, acknowledging the gender differences, there is a gap in literature regarding sustainable fashion consumption from the perspective of female consumers. The purpose of this paper is to reveal the sustainable fashion consumption of females, comparing the clusters of university teachers and students. In doing this, a qualitative research was conducted, with 24 semi-structured interviews in total. The findings revealed a huge contradiction. Although females are aware of sustainable fashion elements, at the same time, they, especially students, do not consider sustainability as a primary motivation for their behaviour. As such, the gap between attitude and behaviour was revealed. Although teachers try to find the good ratio between quality and price, for students, the price usually wins when it comes to purchasing clothes. The representatives from both clusters do shopping from fast fashion retailers; however, students do it much more often and intensively in comparison to teachers. The teachers mainly use swapping and redesigning as sustainable fashion consumption practices. In case of students, second-hand shops and Vinted were prevailing. Among the drivers leading to sustainable consumption, awareness, uniqueness and personal style, and item life-cycle extension were mentioned. Regarding the barriers, high price and low income, personal restrictions, and lack of information and knowledge were mainly emphasised. The findings could be considered to initiate changes, which could enable closing the attitude-behaviour gap.